Curcumin Induces Apoptotic Cell Death via Inhibition of PI3-Kinase/AKT Pathway in B-Precursor Acute Lymphoblastic Leukemia - Kuttikrishnan, Shilpa; Siveen, Kodappully S.; Prabhu, Kirti S.; Khan, Abdul Quaiyoom; Ahmed, Eiman I.; Akhtar, Sabah; Ali, Tayyiba A.; Merhi, Maysaloun; Dermime, Said; Steinhoff, Martin; Uddin, Shahab (Frontiers in Oncology, 2019)
Acute lymphoblastic leukemia (ALL) is a significant cancer of children resulting from the clonal proliferation of lymphoid precursors with arrested maturation. Although chemotherapeutic approaches have been achieving successful remission for the majority of cases of childhood ALL, development of resistance to chemotherapy has been observed. Thus, new therapeutic approaches are required to improve patients prognosis. Therefore, we investigated the anticancer potential of curcumin in ALL. We tested a panel of B-precursor ALL (B-Pre-ALL) cell lines with various translocations after treatment with different doses of curcumin. Curcumin suppresses the viability in a concentration-dependent manner in 697, REH, SupB15, and RS4;11 cells (doses from 0 to 80 μM). Curcumin induces apoptosis in B-Pre-ALL cell lines via activation of caspase-8 and truncation of the BID. Curcumin treatment increases the ratio of Bax/Bcl2 and resulted in a leaky mitochondrial membrane that led to the discharge of cytochrome c from the mitochondria to the cytoplasm, the activation of caspase 3 and the cleavage of PARP. Curcumin treatment of B-Pre-ALL cell lines induced dephosphorylation of the constitutive phosphorylated AKT/PKB and a down-regulation of the expression of cIAP1 and XIAP. Moreover, curcumin mediates its anticancer activity by the generation of reactive oxygen species. Finally, the suboptimal doses of curcumin potentiated the anticancer activity of cisplatin. Altogether, these results suggest an important therapeutic role of curcumin, acting as a growth suppressor of B-Pre-ALL by apoptosis via inactivation of AKT/PKB and down-regulation of IAPs and activation of intrinsic apoptotic via generation of ROS. Our interesting findings raise the possibility of considering curcumin as a potential therapeutic agent for the treatment of B-Pre-ALL.